A novel approach for the energy recovery and position control of a hybrid hydraulic excavator. (April 2020) - Ranjan, Prabhat; Wrat, Gyan; Bhola, Mohit; Mishra, Santosh Kr.; Das, J.
Abstract: The heavy earth moving machineries (HEMM) like hydraulic excavator play a major role in construction and mining industries. In this context, the energy saving strategies in hydraulic excavator needs to be addressed considering its vital importance. Since the hydraulic excavators are subjected to heavy loads, hence the opportunity to harness the potential gravitational energy (GPE) remains a key area which can be effectively explored in order to minimize the energy consumption in consideration with hydraulic excavator. In the projected system, the potential energy is stored as pressure energy in hydro-pneumatic accumulator. The upward movement of the boom is executed with the help of prime mover during the starting of the first duty cycle. In the latter duty cycles, the stored pressurized energy is utilized together with the prime mover energy capable to execute the upward movement of the boom. The position of the boom cylinder is controlled by using the conventional PID controller using proportional flow control valve (PFCV) and accumulator. The error between the actual position and demand position of the linear actuator is minimized along with attainment of superior controlled performance while utilizing Model Predictive Controller (MPC). The pressurized accumulator with PFCV has been utilized to cater the different position demands. This has been also justified both experimentally and analytically with the error in the permissible range of 2%. It has been observed that the proposed system is 10% more efficient in contrast to the conventional system. Highlights: Boom potential energy regeneration using accumulator when actuator move backward. Actuator position control by supplying pressurized stored in accumulator using proportional flow control flow. Energy efficient hydraulic circuit for excavator application. Stability analysis like bode plot, Nyquist plot and Root locus for the designed controller. Increase in energy efficiency up to 10% for a complete duty cycle of proposed circuit compared with conventional circuit.